Localised insulin-induced lipoatrophy in an 8-year-old girl. - Ali, A.; Nicholls, I.; Zidan, A.; Kanji , A. (European Journal of Pediatric Dermatology, 2026)
Lipoatrophy is a rare but clinically significant complication of insulin use, believed to be mediated by immune-complexes. This case describes an 8-year-old Caucasian girl, who presented with a 4-month history of asymptomatic cutaneous depressions at the sites of insulin pump attachment, used to treat her type 1 diabetes mellitus. She was diagnosed with insulin-induced lipoatrophy following ultrasound imaging and skin biopsy of the affected site. Early recognition and management of this complication is essential, not only for its cosmetic implications, but also because insulin absorption from these sites can be unpredictable, leading to poor glycaemic control. Although the incidence of lipoatrophy has markedly declined with the use of modern insulin analogues, isolated cases still occur. In our patient, gradual clinical improvement was observed following a switch in the type of insulin administered via her pump.